Pengiklanan dan kanak-kanak - Totu, Andreas; Halina Sendera Mohd. Yakin; Penerbit Universiti Malaysia Sabah (Kota Kinabalu, Sabah, Malaysia : Penerbit Universiti Malaysia Sabah, 2016)
On advertising and psychological effect to children.
Includes bibliographical references (pages 167-177) and index.
In Malay.
Keywords: Advertising and children; Advertising -- Psychological aspects